Development Life Skills Sport in Indonesia: A Systematic Literature Review - Rizki Burstiando; Amung Ma’mun; Komarudin Komarudin; Yudy Hendrayana (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
In recent years, sport has been seen not only as a means of health, achievement, and industry. More than that sport is considered as a means of developing the whole person. Developing life skills through sports has recently emerged as a study that has been extensively studied in various countries. In Indonesia, studies regarding the development of life skills through sports are still few. This study aims to scientifically reveal the study of life skills through sports in Indonesia through a systematic literature review. Article searches are limited to publications in sports journals in Indonesia over the past 10 years. A total of 18 articles have been found for analysis. The results of the study found 18 articles for further study. The focus of life skills research in Indonesia is more towards life skills improvement programs carried out through coaches for athletes or physical education teachers on school students. It is hoped that further research can expand the focus of studies related to the development of life skills in sports with various research methods to develop improvement programs, measurements, and concepts of life skills in sports